A taxonomic and gross morphological study of freshwater and brakishwater mollusk of Balion River, Ormoc City, Leyte - Romero, Daniel Dennis Granali
Altogether, 20 species of Mollusks were found and identified of the 10 collecting stations that were established along the Balion river, Ormoc City, Leyte of these 8 stations are in Freshwater and 2 from the Brackishwaters.